2008
DOI: 10.1128/jvi.01515-07
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Recombinant Vesicular Stomatitis Virus-Human Immunodeficiency Virus Type 1 Vaccine Vectors by Gene Translocations and G Gene Truncation Reduces Neurovirulence and Enhances Immunogenicity in Mice

Abstract: Recombinant vesicular stomatitis virus (rVSV) has shown great potential as a new viral vector for vaccination. However, the prototypic rVSV vector described previously was found to be insufficiently attenuated for clinical evaluation when assessed for neurovirulence in nonhuman primates. Here, we describe the attenuation, neurovirulence, and immunogenicity of rVSV vectors expressing human immunodeficiency virus type 1 Gag. These rVSV vectors were attenuated by combinations of the following manipulations: N gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
102
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 44 publications
6
102
0
Order By: Relevance
“…Intranasal instillation of VSV into mice leads to initial infection of olfactory receptor neurons and then the olfactory bulb, and this is followed by acute infection of the CNS, breakdown of the blood-brain barrier, and the death of mice (Forger et al, 1991;Bi et al, 1995). Data indicate that attenuation of VSV can occur through genetic modifications of the viral genome (Cooper et al, 2008). Thus, although all four cynomolgus macaques inoculated intrathalamically with 10 7 PFU of wild-type VSV developed signs of neurological disease by days 6-7 after virus inoculation (head tilt, irregular gait, tremors, and ataxia), only one of four macaques receiving recombinant VSV developed clinical and histological signs similar to the wild-type VSV group ( Johnson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Intranasal instillation of VSV into mice leads to initial infection of olfactory receptor neurons and then the olfactory bulb, and this is followed by acute infection of the CNS, breakdown of the blood-brain barrier, and the death of mice (Forger et al, 1991;Bi et al, 1995). Data indicate that attenuation of VSV can occur through genetic modifications of the viral genome (Cooper et al, 2008). Thus, although all four cynomolgus macaques inoculated intrathalamically with 10 7 PFU of wild-type VSV developed signs of neurological disease by days 6-7 after virus inoculation (head tilt, irregular gait, tremors, and ataxia), only one of four macaques receiving recombinant VSV developed clinical and histological signs similar to the wild-type VSV group ( Johnson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We removed the VSV glycoprotein G, the key neurovirulence determinant (20)(21)(22), and replaced it with the arenavirus glycoprotein LCMV-GP (23)(24)(25)(26), thereby generating rVSV(GP). While there are no doses at which wtVSV can be safely introduced into rodent brains, we found that rVSV(GP) caused no significant neurotoxicity even at doses of 10 8 plaque-forming units (PFU).…”
Section: Introductionmentioning
confidence: 99%
“…4 Multiple strategies have been developed to achieve attenuation of the VSV vaccine vector, including truncation of the cytoplasmic tail of the VSV glycoprotein (G) to reduce virulence, as well as modification of other structural proteins. 5 , 6 Alternatively, when the antigen expressed is a glycoprotein that facilitates cell entry, removal and replacement of VSV G with a different viral glycoprotein can occur while preserving the immunogenicity of a replication-competent vector. 7 This strategy has proven effective for the VSV-EBOV vaccine, in which the EBOV glycoprotein (GP) is inserted into a VSV vector from which the G open reading frame is deleted (VSV-ΔG), resulting in a replication-competent virus particle exhibiting rhabdovirus morphology with EBOV GP expressed on its surface (Fig.…”
Section: Introductionmentioning
confidence: 99%